Cambios culturales generados por la religión evangélica en la comunidad nativa Ticuna Bellavista de Callaru, provincia de Ramón Castilla 2021 - Vela Flores, Lydia Stefani (2023)
The research "Cultural changes generated by the evangelical religion in the Ticuna Bellavista de Callaru Native Community, Ramón Castilla Province 2021" in the Loreto region, which responded to the main problem: What are the cultural changes generated by the evangelical religion in the native Ticuna Bellavista de Callaru-Ramón Castilla province 2021? With the arrival of the evangelical religion in the Bellavista Callaru community approximately in the year 2017, it imposed a new form of coexistence, in addition to the appearance of internal conflicts, between the followers of the religion and those who They maintain a traditional lifestyle, disrupting the style of the natives. For this reason, its main objective was to determine the cultural changes generated by the evangelical religion in the aforementioned community. It was a mixed work, with a qualitative and quantitative approach. Having as results that the evangelical religion has generated cultural changes, related to festive practices, clothing, drinks and the collective identity of the Ticuna. At the level of conclusions, it is mentioned that the evangelical religion has weakened the traditions, the sense of belonging, the relationship with nature and the collective identity of the Ticuna. The main changes that have occurred in said territory come from the entry of missionaries in colonial times, the influence of Catholicism and today evangelism.